ANALYSIS OF THE INFLUENCE OF CAREER DEVELOPMENT AND WORK-LIFE BALANCE ON EMPLOYEE TURNOVER INTENTION OF THE MILLENIAL GENERATION WITH JOB SATISFACTION AS INTERVENING VARIABLES IN BPJS HEALTH WEST KALIMANTAN - Sri Wahyuni; Aiyub; Adnan; Marbawi; Yanita (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to determine the effect of career development and work-life balance on turnover intention of millennial generation employees with job satisfaction as an intervening variable at the West Kalimantan Health BPJS. The sample in this study amounted to 91 employees who used the SEM PLS analysis method with WarpPLS software. The results revealed that career development has a positive and significant effect on job satisfaction. Work life balance has a positive and significant effect on job satisfaction. Career development has a positive and significant effect on turnover intention. Work life balance has a positive and significant effect on turnover intention. Job satisfaction has a positive and significant effect on turnover intention. In this study job satisfaction acts as a mediator. Turn over intention can be improved by career development, job satisfaction, and protection for the company's intangible assets.